Prophetic Representation in The Vision of A. Mustafa Bisriâ€™s Poetry Locality - Abdul Wachid B.S. (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto Purwokerto, 2021)
The hallmark of A. Mustofa Bisriâ€™s poetry is the simplicity that is â€œdeceptiveâ€ and the use of words that donâ€™t tend to be aesthetic form. Therefore, this study aims to uncover the intentions of A. Mustofa Bisri in writing poetry. This study was conducted based on field data obtained from interviews with A. Mustofa Bisri at Pesantren Raudlatut Thalibin, Leteh, Rembang, Central Java. The results of this study indicated that the prophetic narrative in A. Mustofa Bisriâ€™s poetry becomes a strength. This is influenced by locality, closely related to sanad of knowledge and transcendental wisdom. Through prophetic narratives and locality (pesantren) as an intensification, A. Mustofa Bisri seeks to â€œliberateâ€ the human soul imprisoned by materialism and industrialization, in addition to strengthening individual monotheistic values.